EDUTAINMENT IN COMPUTER SCIENCE LESSONS: EXPERIENCE OF IMPLEMENTATION IN KREMENCHUK SCHOOLS - Hrytsiuk, Olena; Chernenko, Varvara; Maksymova, Larysa (Physical and Mathematical Education, 2021)
Formulation of the problem. The paper deals with the results of the empirical study of the state of implementation of edutainment, i.e. learning through play, in secondary schools of Kremenchuk. The purpose of the study is to analyze the experience of implementing elements of edutainment in computer science lessons.Materials and methods. To solve the tasks and achieve the goal of the study, a set of methods was used, the main of which are surveys (to identify elements of edutainment used by Kremenchuk teachers of computer science), comparative (to compare the spread of gaming practices in different schools) and mathematical statistics (for quantitative and qualitative analysis of empirical data). The survey was conducted online using Google Forms.Results. Respondents were asked to answer three questions: are they familiar with game learning practices; do they find them useful; which of the practices proposed in the questionnaire they use in the educational process.  Analysis of the results of the survey on the introduction of specific elements of edutainment in the teaching of computer science showed that the most common form is the visualization of educational material using multimedia. Training through competitions is implemented in 12 out of 28 educational institutions. Webquest is involved in computer science lessons in six schools. It is worth noting that together all the elements of game learning proposed in the questionnaire are also used in these six educational institutions. It should be noted that these six educational institutions are the leading Kremenchuk secondary schools. The analysis of the introduction of elements of edutainment in computer science lessons in Kremenchuk secondary schools is carried out for the first time, i.e. this monitoring is only the first step for further, more detailed research. The article contains a set of practical recommendations for the wider introduction of various forms of edutainment in computer science lessons in Kremenchuk schools; in particular, this applies to such a popular form today as a webquest. Teachers’ awareness of the expediency and effectiveness of learning through play allows for the introduction of elements of edutainment.Conclusions. The survey showed that in most educational institutions there are some restrictions on the use of specific forms of edutainment: if the visualization of educational material is used in all schools, then competitive forms of learning and especially web quests need the attention of computer science teachers. The study proves the expediency of a wider introduction of the webquest as a tool to increase the cognitive activity of students, as well as their motivation to study computer science.
Keywords: edutainment; game teaching practices; computer science; Kremenchuk secondary schools; visualization of educational material; competitions; webquest